Non-Financial Reporting in a Function of Growing Social and Environmental Responsibility - A Challenge for Accounting and Auditing - Dmitrović, Veljko; Latinović, Milica; Benković, Sladjana (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
Corporate sustainability and successful long-term business are contributed by the orientation towards achieving economic and financial performance, taking into account social and environmental aspects. On the part of society, there has been a tightening of environmental requirements. The management of a modern company, through achieved economic and environmental performances, indicates that these two interests do not have to be in conflict. Rational use and adequate management of resources reduces operating costs and future liabilities, increases the company's image through increased social responsibility towards the environment. In the process of business decision-making, the importance of environmental accounting and environmental auditing is pointed out, which is based on the measurement of environmental costs and benefits. Environmental accounting represents a very important source of information in the process of managing environmental protection. Modern non-financial reporting has the informational power to incorporate information provided by environmental accounting, and provides added value with financial information, in order to make adequate business decisions in the function of reconciling two goals - making a profit and protecting the environment. The aim of the paper is reflected in the theoretical presentation of non-financial reporting with an emphasis on social and environmental responsibility, and on the review of non-financial information contained in the annual reports of certain companies in the Republic of Serbia whose shares are listed on the Belgrade Stock Exchange. The practical part of the paper refers to the presentation of the methodology and the quality of the non-financial information provided in the reviewed annual reports.
Keywords: environmental accounting; non-financial reporting; annual reports; environmental audit; environmental protection